Effect of dispute resolution strategies on employee performance in the Nigerian banking industry - Tuni, Ijoyah Christopher; Joseph, Okoh Chukwudi (International research journal of management, IT and social sciences, 2022)
This study examined the effect dispute resolution strategies on employee performance in the Nigerian banking industry. Four variables were discussed; compromising strategy, dominating strategy, integrating strategy and avoiding strategy as they affect employee performance in selected banks in Delta State. The sample size for the study was 162 respondents. Simple random sampling technique was adopted. Validated structured sets of questionnaire were used, the primary instruments for data collection. The study adopted descriptive statistics and frequency analysis. Test of hypotheses was done using regression analysis. The study found out that there positive and significant effects of compromising Strategy, integrating strategy, dominating strategy, avoiding strategy and employee performance. The study concluded that avoiding strategy has a major effect on employee performance in Nigeria banking industry and Nigeria banks should improve on integrating strategy, because it would go a long way in enhancing employee performance, that integrity in the banks could have been achieved through strong moral principles and moral uprightness in financial transactions. It is recommended that Efforts should be made by management to organize seminars/workshops on organizational dispute resolution strategy from time to time for the employees.